Who was Rosa Parks? - McDonough, Yona Zeldis (New York : Grosset & Dunlap, 2010)
In 1955, Rosa Parks refused to give her bus seat to a white passenger in Montgomery, Alabama. This seemingly small act triggered civil rights protests across America and earned Rosa Parks the title "Mother of the Civil Rights Movement."
Who was Rosa Parks? -- Down on the farm -- City lights -- Life with Raymond -- The call to action -- Back of the bus -- A visit to Highlander -- A new day -- "No riders today!" -- Moving ahead.
Includes bibliographical references (p. 106).
Keywords: Parks, Rosa, -- 1913-2005 -- Juvenile literature; Parks, Rosa, -- 1913-2005.; African American women -- Alabama -- Montgomery -- Biography -- Juvenile literature; African Americans -- Alabama -- Montgomery -- Biography -- Juvenile literature; Civil rights workers -- Alabama -- Montgomery -- Biography -- Juvenile literature; African Americans -- Civil rights -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; Civil rights workers; Women -- Biography; African Americans -- Biography; African Americans -- Civil rights -- Alabama -- Montgomery -- History -- 20th century; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century; Montgomery Bus Boycott, Montgomery, Ala., 1955-1956.; Race relations; Montgomery (Ala.) -- Race relations -- Juvenile literature; Montgomery (Ala.) -- Biography -- Juvenile literature; Montgomery (Ala.) -- Biography